Effect of lead chloride in a number of physiological variables in the blood of male white rats (Mus-Musculus) - Salwan Yuosif (College of Education for Pure Sciences, 1999)
Abstract The present study is conducted to investigate the effect of lead on some blood components of mice comprising red blood cells (RBC) count, packed cell volume (PCV), hemoglobin concentration (Hb) and blood indices: Mean Corpuscular Volume (MCV), Mean Corpuscular Hemoglobin (MCH) and Mean Corpuscular Hemoglobin Concentration (MCHC). The male animals were divided into three groups (5male/group), the first was given distilled water as control, lead was administered on mice of the 2nd and 3rd groups at (20 and 40 mg/kg respectively), all groups treated daily by gavage needle for a period of 4 weeks. The result revealed significant decrease in (RBC) count, (PCV), (Hb) and blood indices: (MCV), (MCH) and (MCHC). The reduction of the above mentioned parameters was inversely proportional with advancement of treatment and it was more prominent in animals treated with (40 mg/kg) at 4 weeks. This study demonstrated that lead administered orally at repeated doses produced Microcytic hypocromic anemia.